A synergetic effect of sonication with yolk-shell nanocatalyst for green synthesis of spirooxindoles. Issue 2 (3rd April 2021) - Mohammadi, Somaye; Naeimi, Hossein
ABSTRACT: A synergetic effect of ultrasonic irradiation and yolk–shell nanocatalyst was examined for the synthesis of spirooxindoles from isatin, malononitrile and cyclohexanone. It was found this contributory can be accelerated the desired reaction toward obtaining the highly pure products in excellent yields and short reaction times. The nanocatalyst contains the melamine anchored onto magnetic Fe3 O4 nanoparticles were applied as the active base catalyst for the sonication synthesis of spirooxindole compounds. This nanocatalyst has the magnetic core and the very active with great area surface shell. This novel yolk–shell nanocatalyst was prepared through the simple method and characterized by using FT-IR spectrum, X-ray diffraction (XRD), scanning electron microscopy (SEM), thermo gravimetric analysis (TGA), Brunauer–Emmett–Teller (BET) and vibrating sample magnetometer (VSM). The nanocatalyst was used for synthesis of different derivatives of spirooxindoles from under ultrasonic irradiation. GRAPHICAL ABSTRACT: UF0001